Exploration of The Tri Parartha Concept in CSR Programs based on Tri Hita Karana - Lilik Purwanti; Pande Gede Cahyana; Melinda Ibrahim; Zhongqiu Zhao (Jurnal Ilmiah Akuntansi, 2024)
This research focuses on local Balinese wisdom, specifically the Tri Parartha concept within Corporate Social Responsibility (CSR) activities based on Tri Hita Karana (THK). The study aims to explore the concepts of asih (mutual love), punia (mutual assistance), and bhakti (mutual respect) in THK-based CSR programs implemented by various companies in Bali. This qualitative study employs a literature review method to gather and analyze data. The findings indicate significant variations in how companies implement THK-based CSR programs. Generally, the application of THK in CSR encompasses several dimensions: Parahyangan, which includes organizing religious customary ceremonies; Pawongan, which involves providing community or employee assistance programs; and Pelemahan, which focuses on environmental sustainability efforts. Additionally, CSR activities reflecting the Tri Parartha values are evident in these initiatives, emphasizing mutual love, assistance, and respect. This research contributes to the accounting literature by providing a detailed understanding of how local cultural values can be integrated into corporate practices, thereby enhancing the social and environmental impact of CSR activities. These insights are valuable for companies, policymakers, and practitioners seeking to incorporate traditional wisdom into modern business practices, promoting sustainability and community well-being.